18F-FDG-PET in guided dose-painting with intensity modulated radiotherapy in oropharyngeal tumours: A phase I study (FiGaRO). (February 2021) - Michaelidou, A.; Adjogatse, D.; Suh, Y.; Pike, L.; Thomas, C.; Woodley, O.; Rackely, T.; Palaniappan, N.; Jayaprakasam, V.; Sanchez-Nieto, B.; Evans, M.; Barrington, S.; et al.
Highlights: Study of FDG-PET guided dose painting IMRT in high and intermediate risk oropharyngeal cancer. Feasibility of technique across two institutions established. No increase in acute toxicities. Late mucosal toxicity within spectrum of rates reported with standard (chemo)radiotherapy. Image guided radiation dose escalation warrants further investigation. Abstract: Background and purpose: The FiGaRO trial assessed the feasibility and safety of using an FDG-PET-based dose-painting technique to deliver a radiotherapy (RT) boost to the FDG-avid primary tumour in patients with locally advanced high and intermediate risk oropharyngeal cancer. Materials and method: Patients underwent a planning 18FDG-PET-CT scan, immobilised in the treatment position, after one cycle of induction chemotherapy. The volume of persistent FDG-avidity in the primary tumour was escalated to 71.5 Gy in30 fractions delivered using a simultaneous integrated boost Intensity Modulated RT (SIB-IMRT) technique. RT was delivered with concomitant Cisplatin following 2 cycles of induction chemotherapy. The primary outcome was the incidence of grade ≥ 3 late mucosal toxicity 12 months post-treatment, with an excess rate of >10% regarded as unacceptable. Results: Twenty-nine patients were included and twenty-four were treated between 2014 and 2018, in two UK centres. Median follow-up was 36 months (range 4–56 months). Pre-defined planning target volume objectives and organ at risk dose constraints were met in all cases. There were no incidents of acute grade 4 toxicity. There were 4 cases of grade ≥ 3 mucosal toxicity at 12 months post-treatment (19.1%). There were no cases of persistent mucosal ulceration at 12 months. Overall survival at 3-years was 87.5%, 92.9% for intermediate and 70.0% for high risk patients. Conclusion: Late toxicity rates, although higher than anticipated, are comparable to contemporary published data for standard dose chemo-IMRT. Results suggest improved 3y survival rates for high risk patients. This approach merits further investigation. ClinicalTrials.gov Identifier: NCT02953197.